Maternal sepsis in pregnancy and the puerperal periods: a cross-sectional study - Liu, Ping; Zhang, Xiaowei; Wang, Xinxin; Liang, Yiheng; Wei, Nan; Xiao, Zhansong; Li, Ting; Zhe, Ruilian; Zhao, Weihua; Fan, Shangrong (Frontiers in Medicine, 2023)
Maternal sepsis is a life-threatening condition and ranks among the top five causes of maternal death in pregnancy and the postpartum period. Herein, we conducted a retrospective study on sepsis cases to explain the related risk factors by comparing them with bloodstream infection (BSI) and control maternities. In total, 76 sepsis cases were enrolled, and 31 BSI and 57 maternal cases of the same age but with neither sepsis nor BSI were set as controls. Genital tract infection (GTI) and pneumonia were the two most common infection sources in both sepsis (22 cases, 29% and 29 cases, 38%) and BSI cases (18 cases, 58% and 8 cases, 26%). Urinary tract infection (UTI)/pyelonephritis (9 cases, 12%) and digestive infection cases (11 cases, 14%) only existed in the sepsis group. Significantly different infection sources were discovered between the sepsis-death and sepsis-cure groups. A higher proportion of pneumonia and a lower proportion of GTI cases were present in the sepsis-death group (17 cases, 45% pneumonia and 9 cases, 24% GTI) than in the sepsis-cure group (12 cases, 32% pneumonia and 13 cases, 34% GTI). In addition, although gram-negative bacteria were the dominant infectious microorganisms as previously reported, lower proportion of gram-negative bacteria infectious cases in sepsis (30 cases, 50%) and even lower in sepsis-death group (14 cases, 41%) was shown in this study than previous studies. As expected, significantly greater adverse maternal and fetal outcomes, such as higher maternal mortality (26.3% vs. 0% vs. 0%), higher fetal mortality (42.2% vs. 20.8% vs. 0%), earlier gestational age at delivery (26.4 ± 9.5 vs. 32.3 ± 8.1 vs. 37.7 ± 4.0) and lower newborn weight (1,590 ± 1287.8 vs. 2859.2 ± 966.0 vs. 3214.2 ± 506.4), were observed in the sepsis group. This study offered some potential pathogenesis and mortality risk factors for sepsis, which may inspire the treatment of sepsis in the future.